Irisin is inversely associated with intrahepatic triglyceride contents in obese adults - Zhang, Hui-Jie; Zhang, Xian-Feng; Ma, Zhi-Min; Pan, Ling-Ling; Chen, Zheng; Han, Hai-Wei; Han, Cheng-Kun; Zhuang, Xiong-Jie; Lu, Yan; Li, Xue-Jun; Yang, Shu-Yu; Li, Xiao-Ying (Journal of hepatology, 2013)
Obesity is closely related to non-alcoholic fatty liver disease (NAFLD), which has become an important public health problem because of its high prevalence and association with metabolic syndromes. Irisin was recently identified as a novel peptide to improve obesity and glucose homeostasis, and considered to be therapeutic for human metabolic diseases. The aim of this study was to examine the association of serum irisin concentration and liver triglyceride contents in obese Chinese adults. Serum irisin levels were measured and liver fat contents determined by 1H MRS in 296 obese adults. Anthropometric parameters and blood biochemical indexes including liver enzymes, glucose, and lipid profiles were detected. The liver triglyceride contents of subjects were measured by 1H MRS. The protein levels of irisin were determined by quantitative ELISA. We found that serum irisin levels were reduced in obese adults with NAFLD. By dividing the distribution of intrahepatic triglyceride (IHTG) contents into quartiles, serum irisin levels were reduced gradually with the increase of IHTG contents (p<0.01). Higher serum irisin levels were associated with preferable TG levels. Serum ALT and AST concentrations were inversely correlated with serum irisin levels. Multivariate linear regression analysis demonstrated that serum irisin levels were independently associated with liver fat (p<0.01). By logistic regression analysis, the odds ratio for higher IHTG contents was reduced by 12.4% per 1 SD increase in serum irisin concentrations after adjustment for multivariate metabolic factors [OR (95% CI); 0.876 (0.777–0.987)]. These results demonstrated that serum irisin concentrations were inversely associated with the triglyceride contents in the liver and liver enzymes in obese Chinese adults.